Samba II PCR testing for COVID-19 in pregnant women: a retrospective cohort study and literature review - Ruiling Xu; Tara Alicia Pauley; Hannah Missfelder-Lobos; Richard John Haddon; Ravindra Kumar Gupta; Hsu Phern Chong (BMC, 2021)
Abstract Background Asymptomatic carriage of COVID-19 in pregnant women has been reported and could lead to outbreaks in maternity units. We sought to ascertain the impact of rapid isothernal nucleic acid based testing for COVID-19 in an unselected cohort of pregnant women attending our maternity unit. We also assessed the correlation between community prevalence and asymptomatic carriage. Methods Data for the retrospective cohort study were collected from a large UK tertiary maternity unit over a 4-week period using computerised hospital records. Literature searches were performed across multiple repositories. COVID-19 prevalence was extracted from online repositories. Results Nasopharyngeal and oropharyngeal swabs were obtained from 457/465 (98%) women during the study period. The median turnaround time for results was 5.3 h (interquartile range (IQR) 2.6-8.9 h), with 92% of the results returned within 24 h. In our cohort, only one woman tested positive, giving a screen positive rate of 0.22% (1/457; 95% CI: 0.04-1.23%). One woman who tested negative developed a fever postnatally following discharge but was lost to follow-up. From our literature review, we did not find any correlation between asymptomatic carriage in pregnant women and the reported regional prevalence of COVID-19. Conclusions Testing using the SAMBA-II machine was acceptable to the vast majority of pregnant women requiring admission and had a low turnaround time. Asymptomatic carriage is low, but not correlated to community prevalence rates. Screening pregnant women on admission will remain an important component in order to minimise nosocomial infection.